Community Empowerment through Hydroponic Vegetable Farming in Pematang Village, Tigaraksa District, Tangerang Regency - Ignatius Joko Dewanto; Febri Sari Siahaan; Amelia Sholikhaq (The International Journal of Education Management and Sociology, 2025)
Community empowerment is an important strategy in improving the welfare and economic independence of rural communities. One effort that can be made is through hydroponic vegetable cultivation, which has great potential in increasing food production, land efficiency, and increasing community income sources. This study aims to analyze the implementation and impact of community empowerment through hydroponic vegetable cultivation in Pematang Village, Tigaraksa, Tangerang Regency. The P2M approach uses Participatory Action Research (PAR) and qualitative research approaches, including observations, interviews, and related literature studies. The study results indicate that the hydroponic program provides significant benefits in improving community skills in soilless farming, increasing the availability of healthy food, and opening up business opportunities for the local community. In addition, the involvement of farmer groups and support from the local government are important factors in the success of this program. With ongoing assistance and hydroponic-based entrepreneurship training, the Pematang Village community can become more independent and competitive in the modern agricultural sector.